2018
DOI: 10.1007/s13205-018-1386-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of metal oxide nanoparticles on the growth, physiology and metabolic responses in in vitro grown eggplant (Solanum melongena)

Abstract: Nanoparticles (NPs) are widely used in various domestic products and their usage is constantly increasing which in turn can raise several environmental health issues. Like other abiotic stresses, nanomaterials also affect the growth of crop plants. is a common vegetable crop grown in the tropics and subtropics regions with medicinal properties. In this study, was analyzed for its response to three commercially important metallic nanoparticles, namely NiO, CuO, and ZnO, at four different concentrations (100, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 64 publications
0
25
1
Order By: Relevance
“…Hafeez et al [ 87 ] observed that soils amended with copper NPs at concentrations from 10 to 30 ppm significantly increased the growth of wheat. In another study, the root and shoot length of the eggplant seedlings was increased as compared to control plants due to treatment with a lower CuO-NP concentration (100 mg/L) [ 88 ]. The increased length of the seedlings at these concentrations indicates the growth-promoting ability of CuO-NPs at lower concentrations [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hafeez et al [ 87 ] observed that soils amended with copper NPs at concentrations from 10 to 30 ppm significantly increased the growth of wheat. In another study, the root and shoot length of the eggplant seedlings was increased as compared to control plants due to treatment with a lower CuO-NP concentration (100 mg/L) [ 88 ]. The increased length of the seedlings at these concentrations indicates the growth-promoting ability of CuO-NPs at lower concentrations [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TAC increased significantly (12%) in the case of 25 mg/L of chemically synthesized NRs as compared to control. Among biologically synthesized NRs, all concentrations produced a significant (p ≤ 0.05) decline in TAC as compared to positive and negative control [ 36 , 37 ]. The TPC showed a minimum variation between the two sources of NRs, however, the effect of dose was significant ( Figure 7 d).…”
Section: Resultsmentioning
confidence: 99%
“…Details of available literature on any phytotoxicity caused by NPs is also given in Tables 1, 2 and 3. To summarize the available literature, a consensus exists on the application of high concentration of nanomaterials. 20,80,92 This was, for example, illustrated by 40 with plantlets of C. officinalis exposed to AgNPs at 400 mg L À1 . Similarly, phytotoxic effects were observed on seedling of S. melongena 80 treated with 1000 mg L À1 CuO, ZnO or NiO NPs.…”
Section: Negative Impact Of Nanomaterials To Plant Cells and Their Mementioning
confidence: 96%